Solving an equation
In order to solve for c we just have to remember one simple rule: what we do in one side of the equal "=" we should do it in the other side.
In this case:
2c + 7n + z = y
↓ substracting z both sides
2c + 7n + z - z = y - z
2c + 7n + 0 = y - z
2c + 7n = y - z
↓ substracting 7n both sides
2c + 7n - 7n = y - z - 7n
2c + 0 = y - z - 7n
2c = y - z - 7n
↓ dividing by 2 both sides
![\begin{gathered} (2c)/(2)=(y-z-7n)/(2) \\ c=(y-z-7n)/(2) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/1otk2gxae7wizvvdi9u546md569cxsuexu.png)
Then, we have the answer:
![c=(y-z-7n)/(2)](https://img.qammunity.org/2023/formulas/mathematics/college/kkkjvrvhoxsqtik63kgdhz7oyz8m5ffc5d.png)